Finite element analysis of bore pile foundation performance in silty soils of Gorontalo Indonesia - Indriati Martha Patuti; Mohamad Anugrah Ahmad; Fadly Achmad (Journal of Infrastructure Planning and Engineering, 2026)
The development of multi-story buildings on soft soils poses significant challenges in geotechnical design, particularly in tropical regions such as Gorontalo, Indonesia. The development of multi-story buildings on soft soils poses significant challenges in geotechnical design, particularly in tropical regions such as Gorontalo, Indonesia. This study investigates the behavior of bored pile foundations with varying diameters (0.60 m, 0.80 m, and 1.00 m) using the finite element method (FEM) via PLAXIS 2D. The simulation integrates in-situ soil investigation data, including SPT and laboratory tests, with a staged construction model to evaluate total deformation and stress distribution. The borehole profile revealed predominantly silty and silty sand layers with high compressibility and low bearing capacity, requiring precise analysis to mitigate settlement risks. Two loading stages were analyzed: (1) pile installation and (2) column load application with a maximum load of 3,363.3 kN per column. Results show that increasing pile diameter significantly reduces vertical displacement. During pile installation, the total deformation was 4.37 mm for the 0.6 m pile, 4.68 mm for the 0.8 m pile, and 4.19 mm for the 1.0 m pile. Under full column load, displacement reached 35.3 mm (0.6 m), 29.6 mm (0.8 m), and 29.4 mm (1.0 m), respectively. Total stress analyses revealed more concentrated stress beneath the smaller piles and more diffused stress in larger piles. The 1.0 m pile showed the best performance, but the 0.8 m pile offered a comparable result with better material efficiency. This study supports the use of FEM for foundation optimization and provides technical guidance for sustainable infrastructure in soft soil regions.